PENGEMBANGAN MEDIA MIND MAPPING DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA KELAS V - Rikawati, Julia; Mashudi, Mashudi; Suratman, Suratman (Jurnal Visi Ilmu Pendidikan, 2025)
This research aims to develop a mind mapping-based learning media using PowerPoint for Natural and Social Sciences (IPAS) class V elementary school subjects. The method used is Research and Development (R&D) with the ADDIE model until the implementation stage. The research subjects include material experts, media experts, teachers, and grade V students of SDN 21 Reo Behe. The data collection instruments are validation sheets, student response questionnaires, and tests. The results of the study showed that the mind mapping media obtained a very feasible category from material experts (90%), media experts (92.5%), linguists (94%), and teachers (91.25%). Student responses in the limited trial (93.33%) and field (97.08%) categories were very positive. Learning outcomes increased from an average of 48.13 to 85.63 in the posttest with an N-gain of 0.72 in the high category. Thus, mind mapping media has been proven to be valid, practical, and effective in improving students' critical thinking skills.